2011
DOI: 10.1175/2011jcli3876.1
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Precipitation Extremes with Warming in a Cloud-Resolving Model

Abstract: A cloud-resolving model is used to investigate the effect of warming on high percentiles of precipitation (precipitation extremes) in the idealized setting of radiative-convective equilibrium. While this idealized setting does not allow for several factors that influence precipitation in the Tropics, it does allow for an evaluation of the response of precipitation extremes to warming in simulations with resolved rather than parameterized convection. The methodology developed should also be applicable to less i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
206
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(242 citation statements)
references
References 35 publications
23
206
1
Order By: Relevance
“…Upstream of the crest, the increase is 8.8%; in the lee, it is 12.2%. By comparison, precipitation from strong nonorographic storms is generally thought to scale with near-surface water vapor [e.g., Trenberth, 1999;O'Gorman and Schneider, 2009;Muller et al, 2011], which increases by 13.1% in our simulations (column-integrated water vapor increases by 19.7%, owing to greater warming aloft). This suggests that in the absence of dynamical changes, orographic precipitation is likely to increase at a lower rate than intense precipitation in nonmountainous regions.…”
Section: Model Description and Resultsmentioning
confidence: 75%
“…Upstream of the crest, the increase is 8.8%; in the lee, it is 12.2%. By comparison, precipitation from strong nonorographic storms is generally thought to scale with near-surface water vapor [e.g., Trenberth, 1999;O'Gorman and Schneider, 2009;Muller et al, 2011], which increases by 13.1% in our simulations (column-integrated water vapor increases by 19.7%, owing to greater warming aloft). This suggests that in the absence of dynamical changes, orographic precipitation is likely to increase at a lower rate than intense precipitation in nonmountainous regions.…”
Section: Model Description and Resultsmentioning
confidence: 75%
“…The same latent heat release can increase the updraft velocity (Sørland et al 2016). Using a cloudresolving model, Muller and O'Gorman (2011) found that changes in vertical velocities tended to weaken the strength of precipitation extremes despite an increase of upper tropospheric updraft velocities for mixed phased clouds in the tropics.…”
Section: Introductionmentioning
confidence: 96%
“…The CC relation considerably influences the changes in the extreme precipitation intensity under warmer climates (Betts and Harshvardhan 1987;Trenberth et al 2003;Held and Soden 2006;Pall et al 2007;Kharin et al 2007; O' Gorman and Muller 2010;Muller et al 2011;Romps 2011;Westra et al 2014). Considering this, observed relations between extreme precipitation and temperature have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%